The Enzymatic Digestion of Pomaces From Some Fruits for Value-Added Feed Applications in Animal Production - Kithama, Munene; Hassan, Yousef I.; Guo, Keyi; Kiarie, Elijah; Diarra, Moussa S. (Frontiers in Sustainable Food Systems, 2021)
With the noticed steady increase of global demand for animal proteins coupled with the current farming practices falling short in fulfilling the requested quantities, more attention is being paid for means and methods intended to maximize every available agricultural-resource in a highly sustainable fashion to address the above growing gap between production and consumers’ demand. Within this regard, considerable efforts are being invested either in identifying new animal feed ingredients or maximizing the utilization of already established ones. The public preference and awareness of the importance of using waste products generated by fruit-dependent industries (juice, jams, spirits, etc.) has improved substantially in recent years where a genuine interest of using the above waste(s) in meaningful applications is solidifying and optimization-efforts are being pursued diligently. While many of the earlier reported usages of fruit pomaces as feedstuffs suggested the possibility of using minimally processed raw materials alone, the availability of exogenous digestive and bio-conversion enzymes is promising to take such applications to new un-matched levels. This review will discuss some efforts and practices using exogenous enzymes to enhance fruit pomaces quality as feed components as well as their nutrients’ accessibility for poultry and swine production purposes. The review will also highlight efforts deployed to adopt numerous naturally derived and environmentally friendly catalytic agents for sustainable future feed applications and animal farming-practices.